Inequality between women and men in ICD implantation. (August 2022) - Ingelaere, Sebastian; Hoffmann, Ruben; Guler, Ipek; Vijgen, Johan; Mairesse, Georges H.; Blankoff, Ivan; Vandekerckhove, Yves; le Polain de Waroux, Jean-Benoit; Vandenberk, Bert; Willems, Rik
Abstract: Background: The impact of sex on ICD implantation practice and survival remain a topic of controversy. To assess sex-specific differences in ICD implantation practice we compared clinical characteristics and survival in women and men. Methods: From a nationwide registry, all new ICD implantations performed between 01/02/2010 and 31/01/2019 in Belgian patients were analyzed retrospectively. Baseline characteristics and survival rates were compared between sexes. To identify predictors of mortality, multivariable Cox regression was performed. Results: Only 3096 (20.9%) of 14, 787 ICD implantations were performed in women. Within each type of underlying cardiomyopathy, the proportion women were lower than men. The main indication in men was ischemic vs dilated cardiomyopathy in women. Women were overall younger (59.1 ± 15.1 vs 62.6 ± 13.1 years; p < 0.001) and had less comorbidities except for oncological disease. More women functioned in NYHA-class III (33.6% vs 27.9%; p < 0.001) and had a QRS > 150 ms (29.4% vs 24.3%; p < 0.001), consistent with a higher use of CRT-D devices (31.7% vs 25.1%; p < 0.001). Women had more complications, reflected by the need to more re-interventions within 1 year (4.3% vs 2.7%, p < 0.001). After correction for covariates, sex-category was not a significant predictor of mortality (p = 0.055). Conclusion: There is a significant sex-disparity in ICD implantation rates, not fully explained by epidemiological differences in the prevalence of cardiomyopathies, which could imply an undertreatment of women. Women differ from men in baseline characteristics at implantation suggesting a selection bias. Further research is necessary to evaluate if women receive equal sudden cardiac death prevention.